ANALISIS DETERMINAN IMPLEMENTASI SISTEM AKUNTANSI INSTANSI BERBASIS AKRUALDAN IMPLIKASINYA TERHADAP EFEKTIFITAS KERJASATUAN KERJA KOMISI PEMILIHAN UMUM - Yessy Puturuhu Iriene Puturuhu; Hermanto - -; Lilik Handajani (InFestasi, 2016)
This research aims to examinethe influences of information quality, system quality, and service quality ofthe user satisfaction of the Agency Accrual-Based Accounting Systems (SAIBA). In addition, it will alsoexamine the influence of user satisfaction toward the user effectiveness particularly at ElectionCommittee of West Nusa Tenggara Province (KPU NTB). This research uses purposivesamplingtechnique with a sample of 66 respondents. A path analysis model which has been conducted bymodifying DeLone and McLean model is used to test the hypothesis.The results show that system quality and service quality have a positive influence on user satisfaction,whereas information quality has no influence on user satisfaction. It is also found that user satisfactionhas a significant influence on effectiveness of the user.This research provides important implications fora successful implementation of SAIBA which is influenced by user satisfaction of information system. Thesystem quality which is reliable, flexible, user-friendly, accessible, and secure plays an important rule inimproving user satisfaction. Moreover, the service that provided by KPPNsuch as willingness to help,understanding, and respondsiveness to the needs of user has an impact on increasing user satisfaction.